Preparation, characterization and cell labelling of strong pH-controlled bicolor fluorescence carbonized polymer dots. Issue 3 (5th January 2022) - Liu, Zengchen; Wang, Like; Wang, Baodui; Chen, Yahong; Tian, Fengshou; Xue, Yingying; Li, Yanxia; Zhu, Wenping; Yang, Weijie
Abstract : Multicolor fluorescence N-doped CPDs from dextrin water solution in strong acidic and alkaline environments were synthesized and characterized, which revealed that pH value plays a vital role in the process of CPD growth. Abstract : As a class of important carbon nanomaterial, carbonized polymer dots (CPDs), also called carbon dots (CDs), have aroused wide interest owing to their unique water solubility, fluorescence properties, and rich surface functional groups. However, the directional tuning of the fluorescence properties of CPDs remains incomplete because of the influence of many factors like diameter, solvent and surface groups. Particularly, most carbonized polymer dots are synthesized in a neutral pH environment. Herein, by modulating the pH (strongly acidic or alkaline) of dextrin water solution, bicolor fluorescence emission (blue and yellow) CPDs were prepared by a hydrothermal reaction. Through systematic characterization, it was found that the different fluorescence properties are regulated by the diameters and surface groups of the carbon cores. Simultaneously, the pH value affected the nucleation process. Based on the excellent fluorescence properties, cell fluorescence imaging and cytotoxicity were tested. The bicolor fluorescence CPDs obtained by tuning the pH provide an important theoretical basis for the design of broadband CPDs.